Facile synthesis of ternary PtPdCu alloy hexapods as highly efficient electrocatalysts for methanol oxidation. Issue 21 (30th March 2020) - Gao, Na; Wu, Xingqiao; Li, Xiao; Huang, Jingbo; Li, Dongsheng; Yang, Deren; Zhang, Hui
Abstract : PtPdCu hexapods with tunable compositions were synthesized and exhibited substantially enhanced catalytic properties for MOR relative to Pt/C. Abstract : Developing an efficient Pt-based multimetallic electrocatalyst with well-defined shapes for methanol oxidation reaction (MOR) is critical, however, it still remains challenging. Here we report a one-pot approach for the synthesis of ternary PtPdCu alloy hexapods with different compositions. Their MOR activities increased in the sequence Pt2 PdCu4 < Pt3 PdCu4 < Pt5 PdCu5, and were substantially higher than that of commercial Pt/C. Specifically, the Pt5 PdCu5 hexapods exhibited the highest mass (0.97 mA μgPt −1 ) and specific (7.39 mA cm −2 ) activities towards MOR, and were 5.4 and 19.4 times higher than those of commercial Pt/C (0.18 mA μgPt −1 and 0.38 mA cm −2 ), respectively. This enhancement could be probably attributed to the bifunctional mechanism and ligand effect through the addition of Cu and Pd as well as the unique dendritic structure. The better tolerance for CO poisoning also endowed the PtPdCu hexapods with superior durability relative to commercial Pt/C.